Social Capital of Madura Tribe in Entrepreneurship - Bahagia Bahagia; Endin Mujahidin; Abdul Karim Halim; Rimun Wibowo; Abdullah Nuruz Zaini; Ainiyah Hidayanti Yusup; Siti Zulfah Jaelillah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study intends to find the social capital of the Madurese community who own a business in Bogor, West Java. The research method used is qualitative, while the sampling was carried out purposively based on the consideration that the respondents taken must already have a business in Bogor. The results show that the Madurese interviewed had strong social capital through religious recitations. The purpose of religious studies is to maintain a friendship with other members of the Madurese community, although the main goal is to discuss religion. Social life is also supported by mutual assistance activities between them so that someone who is struck by a disaster will be assisted by other members. People who are affected by disasters such as death will be assisted by other members even though they are not close relatives but are still of the same tribe, namely the Madura tribe. They will work hand in hand to raise money and give it to a grieving family. In addition, the people of Madura have a very good character in trying because they are hard workers, never give up, and are consistent. Meanwhile, the businesses that are mostly engaged in are scrap metal trading, business figures, satay entrepreneurs, and furniture.